PDGFRB mutation and tyrosine kinase inhibitor resistance in Ph-like acute lymphoblastic leukemia - Zhang, Yingchi; Gao, Yufeng; Zhang, Hui; Zhang, Jingliao; He, Fuhong; Hnízda, Aleš; Qian, Maoxiang; Liu, Xiaoming; Gocho, Yoshihiro; Pui, Ching-Hon; Cheng, Tao; Wang, Qianfei; et al. (Blood, 2018)
Philadelphia chromosome (Ph)-like acute lymphoblastic leukemia (ALL) comprises ∼10% to 15% of childhood ALL cases, many of which respond exquisitely to tyrosine kinase inhibitors (TKIs), for example, imatinib in PDGFRB-rearranged ALL. However, some cases developed drug resistance to TKIs and the mechanisms are poorly understood. In this study, we identified a novel PDGFRB fusion gene, namely AGGF1-PDGFRB, and functionally characterized its oncogenic potential in vitro. Further genomic profiling of longitudinally collected samples during treatment revealed the emergence of a mutation, PDGFRBC843G , which directly conferred resistance to all generations of ABL TKIs, including imatinib, dasatinib, nilotinib, and ponatinib. PDGFRB-mutant leukemia cells are highly sensitive to multitarget kinase inhibitor CHZ868, suggesting potential therapeutic options for some patients resistant to ABL TKIs. In summary, we describe a complex clonal evolution pattern in Ph-like ALL and identified a novel PDGFRB point mutation that drives leukemia relapse after ABL TKI treatment.
Keywords: angiogenní proteiny; předškolní dítě; Humans; Mutation; Recurrence; Oncogene Proteins, Fusion; Antineoplastic Agents; nádorové buněčné linie; Angiogenic Proteins; Receptor, Platelet-Derived Growth Factor beta; chemorezistence; Whole Genome Sequencing; protinádorové látky; mužské pohlaví; Protein Kinase Inhibitors; růstový faktor odvozený z trombocytů - receptor beta; Child, Preschool; inhibitory proteinkinas; Precursor Cell Lymphoblastic Leukemia-Lymphoma; výsledek terapie; fúzní onkogenní proteiny; Drug Resistance, Neoplasm; recidiva; Treatment Outcome; sekvenování celého genomu; akutní lymfatická leukemie; lidé; mutace; Male; Cell Line, Tumor